Investigation of effects of boron additives and heat treatment on carbides and phase transition of highly alloyed duplex cast iron - Tasgin, Yahya; Kaplan, Mehmet; Yaz, Mehmet (Elsevier Sci Ltd, 2009)
The effect of boron additives and heat treatment on the microstructural morphology of the transition zone in a duplex cast iron, which has an outer shell of white cast iron (with a high Cr-content and containing boron additives) and an inner side composed of normal gray cast iron, has been investigated. For this purpose, two experimental materials possessing different compositions of white-gray duplex cast iron were produced. Subsequently, metallographic investigations were carried out to study the effect of heat treatment applied to the experimental materials by using the scanning electron microscopy technique, along with optical microscopy and energy dispersive X-ray spectroscopy. Moreover, the formation of various phases and carbide composites in the samples and their effects on the hardness were also investigated using X-ray diffraction techniques. The results of investigations, and hardness showed that addition of the elements Cr and B to high-alloyed white cast iron affected carbide formation significantly, while simultaneously hardening the microstructure, and consequently the carbide present in the transition area of white-gray cast iron was spread out and became thinner. However, B additives and heat treatment did not cause any damage to the transition region of high Cr-content duplex cast iron. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: White-gray duplex casting; Cast iron; Chromium; Microstructure